The tax judiciary is a guarantee of economic rights and freedoms in Iraq - محمد, محمد علوم; طعمة, زينب سعدون (Journal of Legal Sciences, 2021)
The tax legal system, with its rules relating to imposing and assessing the tax and how to collect it, is one of the issues that the taxpayer is keen to follow-up on and caring about, but the aforementioned system is contested by two conflicting interests, the taxpayer’s interest in the view of a money-cutter and a means of always depriving of his wealth to the tax-imposing authority that It seeks to ensure the regular and steady flow of financial resources to the public treasury, which necessitates the presence of a judicial body entrusted with the task of securing a balance between these two conflicting interests from issues that consider themselves strongly in the tax field. It is one of the oldest human rights and public freedoms, and it is one of the oldest rights that originated, as it appeared with the transition of people from the hunting stage to the stage of grazing and agriculture, which was associated with ownership and the presence of the human need to exchange goods with others. Humanitarian about the rights and freedoms of the financial authority and its authority.